Pertumbuhan Ekonomi Masyarakat di Pinggiran Kota - Rusdha, Ulya; Elizabeth, Misbah Zulfa (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to see how the economic growth of the people of Mranggen District develops, find the factors that affect it, and find the most suitable development strategy to encourage more equitable and sustainable economic growth. Research methodology: This research method is a qualitative method using a qualitative approach of case studies, which is taken because this research is very interesting to study. As well as with interview techniques in collecting information. Results: Mranggen District, as a suburb of Semarang City, experienced significant economic growth thanks to its economic linkages with the surrounding city and districts, as well as developing through small and medium industries, trade, and agriculture, which encouraged land use change and urban development. Limitations: This research is limited to Mranggen District in Demak Regency, so the results may not be generalized to other areas. In addition, qualitative interview methods and data limitations can affect the subjectivity and completeness of the information obtained. Contributions: This research expands the understanding of the impact of economic growth and urbanization on suburban areas, especially in Mranggen District, as well as identifying opportunities for small and medium enterprises in the area. These findings also provide valuable data for further study and provide important insights for policymakers in designing economic and infrastructure development strategies.